Enhanced woody biomass production in a mature temperate forest under elevated CO2 - Neil Loader (Nature Climate Change, 2024)
Enhanced CO2 assimilation by forests as atmospheric CO2 concentration rises could slow the rate of CO2 increase if the assimilated carbon is allocated to long-lived biomass. Experiments in young tree plantations support a CO2 fertilization effect as atmospheric CO2 continues to increase. Uncertainty exists, however, as to whether older, more mature forests retain the capacity to respond to elevated CO2. Here, aided by tree-ring analysis and canopy laser scanning, we show that a 180-year-old Quercus robur L. woodland in central England increased the production of woody biomass when exposed to free-air CO2 enrichment (FACE) for 7 years. Further, elevated CO2 increased exudation of carbon from fine roots into the soil with likely effects on nutrient cycles. The increase in tree growth and allocation to long-lived woody biomass demonstrated here substantiates the major role for mature temperate forests in climate change mitigation.